KEKERASAN TERHADAP ANAK PERSPEKTIF HAM DAN HUKUM ISLAM SERTA UPAYA PERLINDUNGANNYA - Syukron Mahbub (Ulumuna: Jurnal Studi Keilsman, 2015)
The violence against children can occurred anywhere and anytime, and it was also as a human right violation against children which cannot be justified either in the perspective of Human Right and Islamic law. despite the fact that they are often overlooked. Therefore it needs a strategic step to handle it. The handling problem of violence victim children should be done together because violence is a crucial problem, it cannot be solved only by one stakeholder, it needs to divide the role and creates the clear mechanism and responsibility of all related sector, such as government, komnas HAM, KPAI, PPT, LSM, social organization, university, mass media, professional institution, law enforcement, politician, social leaders, and family, social and children environment. The most important thing is the whole commitment to fight save them. Because children is not only the heir and generation , but same time as the owner and manager of the future